Highly efficient oxygen evolution reaction via facile bubble transport realized by three-dimensionally stack-printed catalysts - Kim, Ye Ji; Lim, Ahyoun; Kim, Jong Min; Lim, Donghoon; Chae, Keun Hwa; Cho, Eugene N.; Han, Hyeuk Jin; Jeon, Ki Ung; Kim, Moohyun; Lee, Gun Ho; Lee, Gyu Rac; Ahn, Hyun S.; et al. (Nature Publishing Group, 2020)
Despite highly promising characteristics of three-dimensionally (3D) nanostructured catalysts for the oxygen evolution reaction (OER) in polymer electrolyte membrane water electrolyzers (PEMWEs), universal design rules for maximizing their performance have not been explored. Here we show that woodpile (WP)-structured Ir, consisting of 3D-printed, highly-ordered Ir nanowire building blocks, improve OER mass activity markedly. The WP structure secures the electrochemically active surface area (ECSA) through enhanced utilization efficiency of the extended surface area of 3D WP catalysts. Moreover, systematic control of the 3D geometry combined with theoretical calculations and various electrochemical analyses reveals that facile transport of evolved O-2 gas bubbles is an important contributor to the improved ECSA-specific activity. The 3D nanostructuring-based improvement of ECSA and ECSA-specific activity enables our well-controlled geometry to afford a 30-fold higher mass activity of the OER catalyst when used in a single-cell PEMWE than conventional nanoparticle-based catalysts. Improved design of three-dimensionally nanostructured catalysts for oxygen evolution reaction (OER) can play a key role in maximizing the catalytic performance. Here, the authors show that woodpile-structured iridium consisting of 3D-printed, highly-ordered nanowire building blocks significantly improve OER mass activity.